Prevalence and Risk Factors of Chronic Kidney Disease - Xasanova, Nargis Qodirovna (American Journal of Bioscience and Clinical Integrity, 2024)
Chronic kidney disease (CKD) is characterized by kidney damage lasting three months or more under the influence of various etiological factors, and its dysfunction as a result of replacement of its normal anatomical structures with fibrosis. Chronic Kidney Disease (CKD) is a progressive condition in which the kidneys gradually lose their ability to function effectively over time. CKD can lead to kidney failure, making it a serious health issue that often requires lifelong management and involves a progressive loss of kidney function, often leading to the need for renal replacement therapy, such as dialysis or transplantation. The 2012 KDIGO CKD classification considers the underlying cause and categorizes CKD into 6 stages of progression and 3 stages of proteinuria based on glomerular filtration rate and levels of albuminuria. Although the causes of CKD vary, certain disease processes exhibit similar patterns.